2012
DOI: 10.1016/j.elecom.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of MoS2 on ordered mesoporous carbon nanospheres: A highly active catalyst for electrochemical hydrogen evolution

Abstract: An efficient electrocatalyst for hydrogen evolution has been developed based upon in situ reduction of MoS 2 on ordered mesoporous carbon nanospheres (MoS 2 /MCNs). The properties of MoS 2 /MCNs were characterised by scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. Polarisation curves and electrochemical impedance measurements were obtained for MoS 2 /MCNs modified glassy carbon electrodes. The MoS 2 /MCNs exhibit high catalytic activity for hydrogen evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 20 publications
(26 reference statements)
0
75
0
Order By: Relevance
“…However, we found that contamination could be drastically reduced by depositing a small amount of nanoscale crystallites of two-dimensional MoS 2 onto the graphene samples prior to proton irradiation (see Methods for details). The effect of MoS 2 presence is clear from comparing the two low-magnification images in The exact mechanism behind this curious cleaning effect of MoS 2 is not known but we speculate that it is likely to be due to the known catalytic activity of MoS 2 with respect to hydrogen evolution 53,54 which helps cracking the hydrocarbons on the graphene surface without the need of annealing. The samples were irradiated using a 500 kV ion implanter using 350 keV protons at a total ion fluence of 2·10 16 ions/cm 2 .…”
Section: Resultsmentioning
confidence: 96%
“…However, we found that contamination could be drastically reduced by depositing a small amount of nanoscale crystallites of two-dimensional MoS 2 onto the graphene samples prior to proton irradiation (see Methods for details). The effect of MoS 2 presence is clear from comparing the two low-magnification images in The exact mechanism behind this curious cleaning effect of MoS 2 is not known but we speculate that it is likely to be due to the known catalytic activity of MoS 2 with respect to hydrogen evolution 53,54 which helps cracking the hydrocarbons on the graphene surface without the need of annealing. The samples were irradiated using a 500 kV ion implanter using 350 keV protons at a total ion fluence of 2·10 16 ions/cm 2 .…”
Section: Resultsmentioning
confidence: 96%
“…To improve their performance, MoS 2 are usually used as additive in functionalized carbon materials [30,39e41]. The strong chemical interactions between Mo precursors and functional group allowed the selective growth of MoS 2 nanoparticles on the carbon materials [39,40]. The advantages of Nedoping in carbon materials for HER were also confirmed by MoS 2 eNCNF nanomaterials and MoS 2 /Nedoped rGO composites, demonstrating the superiority of nitrogen doping in improving the HER activity [30,40].…”
Section: Introductionmentioning
confidence: 93%
“…Accordingly, MoS 2 nanoparticles grown on reduced graphene oxide (rGO) sheets 17 , low crystalline MoS 2 nanosheet coated carbon nanotubes (CNTs) 18 , two-dimensional hybrid nanosheets of tungsten disulfide and rGO 19 , MoS x grown on graphene-protected three-dimensional Ni foams 20 and MoS 2 on ordered mesoporous carbon nanospheres 21 have been fabricated for HER. Apart from introducing an excellent electron pathway between substrate electrode and catalyst, the nanostructured support also provides a large surface area for facile contact with the electrolyte and homogeneous dispersion of catalysts free from aggregation.…”
Section: Introductionmentioning
confidence: 99%